Prevalence, risk factors and character of abdominal hernia in Arar City, Northern Saudi Arabia in 2017 - AhmedAlenazi, Abdulmajeed (Electron Physician, 2017)
BACKGROUND: Abdominal wall hernias are a very common surgical condition affecting all ages and both sexes. The main risk factors of hernias include pregnancy, weight lifting, constipation, and weight gain. OBJECTIVE: The aim of this study was to determine the prevalence and risk factors of abdominal hernias, their causes, treatment and complications among both sexes of the Arar population (Saudi Arabia). METHODS: A cross-sectional study was conducted among 1,567 adults living in Arar city in 2017. Data was collected by personal interview via questionnaire translated into Arabic, and general and local examination. Data were analyzed by SPSS version 16, using descriptive statistics and Chi Square test. RESULTS: The overall prevalence of abdominal hernias was 11.7%, hernias were more prevalent in females than in males (63.4% vs. 36.6%), the most common cases were para-umbilical 33.9%, inguinal 27.3%, and umbilical in 20.8% of the cases, 51.9% were obese, 53.6% had previous abdominal surgery, 19.1% had previous abdominal trauma, 28.4% had positive family history of hernia and 39.9% were grand multipara. Hernias were significantly affected by sex, obesity, previous abdominal surgery, previous abdominal trauma, positive family history of hernias and being grand multipara (p<0.05). Treatment of hernias was surgical in 47.5% and conservative in 47.0%, complications occurred in 20.2% and 25.1% were recurrent after treatment. CONCLUSION: Abdominal wall hernias are a common clinical presentation in Arar, KSA. Abdominal hernias are more common in women than men, there is an obvious relationship between obesity and hernias. Early diagnosis, easily accessible health facilities and health education are important to prevent complications. New modality of treatment should be adopted as the standard choice of care to prevent recurrence.